Beyond Organisational Borders: The Soft Power of Innovation in the Health Sector; Comment on "What Managers Find Important for Implementation of Innovations in the Healthcare Sector - Practice Through Six Management Perspectives" - Cátia Miriam Costa (Kerman University of Medical Sciences, 2022)
Health is not just a physiological state, it is also a relational phenomenon. This means health is a collective challenge, often a cross-border one. Diplomacy in the health sector has progressively received more attention from formal actors (national states, international organisations, etc) but after the coronavirus disease 2019 (COVID-19) challenge, this attention became a global emergency mobilising an expansive set of knowledge-seeking players (industry, research networks, civil society, etc). This paper comments on and leverages the contribution by Palm and Feschier on innovation management at the organisational level to address a complementary dimension: the internationalization process, and the need for a particular set of skills and routines to make innovations travel through different markets and regulatory contexts. Our argument is that marketing (knowing about customers) and diplomacy (understanding framing institutions) constitute a set of dynamic capabilities (soft power) that are critical for the effective internationalization of innovation.